PERBANDINGAN HASIL LAJU ENDAP DARAH METODE WESTERGREN DENGAN MENGGUNAKAN ANTIKOAGULAN EDTA DAN NATRIUM SITRAT 3,8% PADA WANITA MENSTRUASI - Puji Lestari Atsania Putri; Handayati Anik; Endah Astuti Sri Sulami (Jurusan Teknologi Laboratorium Medis Poltekkes Kemenkes Surabaya, 2021)
The Erythrocyte sedimentation rate is a routine blood test performed to monitor the course of the disease where high values ​​are likely to be associated with the presence of inflammation. ICSH (International Council for Standardization in Hematology) recommends the Westergren method as a method for examining LED with several developments in terms of the anticoagulants and diluents used. Anticoagulants that can be used are Sodium Citrate 3,8% anticoagulant and EDTA (Ethylene Diamine Tetra-Acetid-Acid) anticoagulant. This study aims to determine the differences in the erythrocyte sedimentation rate of the westergren method using EDTA anticoagulants and sodium citrate 3.8%.This study uses primary data collection techniques with comparative research type. The research was conducted at the Health Analyst Laboratory of Poltekkes Kemenkes Surabaya, in January-April 2021. The sample of the study was 50 menstruating women who had met several criteria, who would be examined for LED values ​​using the Westergren method using EDTA anticoagulants in purple vacuum tubes and sodium citrate 3,8 % on a black vacuum tube.The results showed that the mean of sedimentation rate with EDTA anticoagulant was 27.66 mm/hour and 22.04 mm/hour for sodium citrate 3,8% anticoagulant. The statistical test was carried out by using the paired sample t-test which showed the sig (p) value = 0.000 0.05, so it could be concluded that there was a difference between the EDTA anticoagulant LED and the sodium citrate anticoagulant LED. Thus the EDTA anticoagulant can still be used as an anticoagulant in examining the erythrocyte sedimentation rate